Graphene-based optical waveguide tactile sensor for dynamic response. Issue 1 (December 2018) - Kim, Jin; Choi, Hongkyw; Shin, EunJin; Park, Suntak; Kim, In
Abstract Optical tactile sensors based on a directional coupler have been widely investigated because of their many advantages. However, one important requirement limits their wide application: the refractive index of the upper superstrate must be equal to or larger than that of the optical waveguide core. To overcome this disadvantage, an optical waveguide tactile sensor using graphene is proposed and its operational feasibility was validated experimentally. The pressure-dependent lateral deformation of the low-index prism-like microstructure on an elastomer superstrate has a key role in optically measuring the mechanical pressure. By mechanically varying the lateral deformation area, the waveguide core-graphene-polydimethylsiloxane (PDMS) interface area was adjusted and the amount of light absorption by graphene became tunable, even when the refractive index of the superstrate was lower than that of the waveguide core. The dynamic response of the sensor was accurately matched to the repeated pressing and release time of the pressure, and exhibited a real-time response to multi-stepped mechanical pressing and releasing using a piezoelectric motor. The proposed graphene-based optical tactile sensor is foundational to the use of a wide range of materials for overcoming the shortcoming of a directional coupler-based optical tactile sensor.